Kidney Transplantation From Hepatitis C Viremic Deceased Donors to Aviremic Recipients in a Real-world Setting. Issue 10 (October 2021) - Concepcion, Beatrice P.; Binari, Laura A.; Schaefer, Heidi; Rega, Scott; Feurer, Irene; Shawar, Saed; Naik, Ruchi; Hickman, Laura; Walker, Jasmine; Kapp, Meghan; Birdwell, Kelly A.; Langone, Anthony; et al.
Abstract : Background: Transplantation of hepatitis C viremic (HCV+) deceased donor kidney transplants (DDKT) into aviremic (HCV–) recipients is a strategy to increase organ utilization. However, there are concerns around inferior recipient outcomes due to delayed initiation of direct-acting antiviral (DAA) therapy and sustained HCV replication when implemented outside of a research setting. Methods: This was a retrospective single-center matched cohort study of DDKT recipients of HCV+ donors (cases) who were matched 1:1 to recipients of HCV– donors (comparators) by age, gender, race, presence of diabetes, kidney donor profile index, and calculated panel-reactive antibody. Data were analyzed using summary statistics, t-tests, and chi-square tests for between-group comparisons, and linear mixed-effects models for longitudinal data. Results: Each group consisted of 50 recipients with no significant differences in baseline characteristics. The 6-mo longitudinal trajectory of serum creatinine and estimated glomerular filtration rate did not differ between groups. All recipients had similar rates of acute rejection and readmissions (all P  > 0.05). One case lost the allograft 151 d posttransplant because of acute rejection, and 1 comparator died on postoperative day 7 from cardiac arrest. HCV+ recipients initiated DAA on average 29 ± 11 d posttransplant. Ninety-eight percent achieved sustained virologic response at 4 and 12 wks with the first course of therapy; 1 patient had persistent HCV infection and was cured with a second course of DAA. Conclusions: Aviremic recipients of HCV+ DDKT with delayed DAA initiation posttransplant had similar short-term outcomes compared with matched recipient comparators of HCV– donors.